Por trás da qualidade: inter-relações das Relações Públicas e os sistemas de gestão de qualidade - Silva, Vitor Amaral Magno da [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
This study examines some characteristics of the contemporary reality and its influence on the dynamics of the organizational activities, in particular, related to the quality management. Discusses capitalist logic of maximization of profits that has been sophisticated in face of new scenarios that arise with society evolution. It also proposes a reflection on the philosophies and formats of management that fits with the desire to meet the needs of society through the expansion of quality - now a reference for the production processes and management systems. The work highlights the relations between communication and quality, pointing them as fundamental to the use of fissures on the evolution of the capitalist system in developing programs, philosophies and management systems. The intention is to turn able ways to contemplate the needs and interests of the largest number of public and variables in a different relation than the usual, in which a few wins and many lose

Este estudo analisa algumas características da realidade contemporânea e suas influências na dinâmica das atividades das organizações, em especial, às relacionadas à gestão de qualidade. Discute a lógica capitalista da maximização dos lucros que tem se sofisticado diante dos novos cenários que surgem com a evolução da sociedade. Propõe ainda uma reflexão sobre as filosofias e formatos de gestão que se insere com a pretensão de atender os anseios da sociedade por meio da ampliação da qualidade – agora uma referência para os processos produtivos e sistemas de gestão. O trabalho destaca as relações entre a comunicação e qualidade apontando-as como fundamentais para a apropriação das brechas da evolução do sistema capitalista na elaboração de programas, filosofias e sistemas de gestão. A intenção é propor a viabilização de formas para contemplar as necessidades e interesses do maior número de públicos e variáveis, numa relação distinta da usual, na qual poucos ganham e muitos perdem
Keywords: Empresas; Qualidade - Administração; Controle de qualidade; Comunicação; Administração - Filosofia; Business enterprises; Quality control; Communication; Management - Philosophy